Elicitor-mediated enhancement of secondary metabolites in plant species: a review - Razzaq, Abdul; Zafar, Muhammad Mubashar; Ali, Aima; Ihsan, Lubna; Qadir, Fariha; Khan, M. Nasir; Zhang, Yingying; Gao, Linmao; Cong, Hanqing; Iqbal, Rashid; Jiang, Xuefei; Qiao, Fei (Frontiers in Plant Science, 2025)
Plant metabolites play a vital role in a plant’s defense system. Plant metabolites are extensively studied for their therapeutic values. Plant therapeutic values are attributed based on the magnitude of metabolites. Among all the metabolites, secondary metabolites are considered to have more potential. Different medicinal plants like Cephalotaxus contain therapeutically valuable bioactive alkaloids. The pharmaceutical relevance of secondary metabolites has been well recognized, but low accumulation and convoluted biosynthetic mechanism hamper their industrial production. Elicitors, both biotic and abiotic, have emerged as effective strategies to enhance metabolite biosynthesis by triggering plant defense signaling pathways. Chemical agents like salicylic acid, methyl jasmonate, nitric oxide, and heavy metals, along with physical factors such as ultraviolet radiation, salinity, and osmotic stress, significantly increase secondary metabolite production. Similarly, microbial extracts, polysaccharides, and polyamines serve as potent biotic elicitors. Synergistic combinations, particularly sodium fluoride with methyl jasmonate, have shown remarkable success in boosting Cephalotaxus alkaloid yields. Advances in elicitor-mediated interventions, coupled with omics, nanotechnology, and CRISPR-based bioprocessing, promise sustainable and scalable production systems. This review highlights the mechanisms, case studies, challenges, and prospects of elicitor applications, emphasizing their transformative role in bridging traditional medicinal plants with modern pharmaceutical needs.